Characterizing novel ripening related genes linked to shelf life in tomato - Thomas, Michael (2016)
Fruits play a major role in maintaining a healthy diet and have been shown to reduce instances of heart disease, osteoporosis and cancer. However, the perishable nature of fruits leads to an increased cost and decrease in quality of post-harvest food. A significant crop improvement stratagem is focused toward fruit which retain their health promoting attributes whilst improving quality and reducing post-harvest waste. To provide new insights into the genetic regulation of fruit ripening we have characterised novel ripening related genes linked to shelf life in tomato, the tetraspanins, a zinc-finger protein, and a heat-shock transcription factor. The tetraspanins are highly conserved integral membrane proteins that act as ligands for extracellular molecules to form tetraspanin-enriched micro-domains which influence cell-cell adhesion, intercellular communication, and plant development. Transgenic tomato lines were generated to determine the role of the tetraspanins in fruit ripening. First and foremost, upregulation of the SlTET-6 gene had no obvious ripening phenotype whilst overexpression or silencing of the SlTET-8 gene appeared to be lethal in tomato, most likely due to the importance of these genes in plant development. A zinc-finger protein and a heat-shock transcription-like factor were identified as targets of LeMADS-RIN and investigations using constitutive knock-down constructs have shown an increase in fruit firmness in tomato at the Breaker+4 and red-ripe stages of ripening. RNA-seq revealed differential expression of over 4000 ripening related genes associated with silencing which included polygalacturonase, pectinmethylesterase, and pectate lyase. These data emphasise the role of transcriptional regulation in fruit ripening and provide a novel means of regulating fruit development.